Dysbiosis and extraintestinal cancers - Ruishan He; Pingqian Qi; Linzhen Shu; Yidan Ding; Peng Zeng; Guosheng Wen; Ying Xiong; Huan Deng (Journal of Experimental & Clinical Cancer Research)
Abstract The gut microbiota plays a crucial role in safeguarding host health and driving the progression of intestinal diseases. Despite recent advances in the remarkable correlation between dysbiosis and extraintestinal cancers, the underlying mechanisms are yet to be fully elucidated. Pathogenic microbiota, along with their metabolites, can undermine the integrity of the gut barrier through inflammatory or metabolic pathways, leading to increased permeability and the translocation of pathogens. The dissemination of pathogens through the circulation may contribute to the establishment of an immune-suppressive environment that promotes carcinogenesis in extraintestinal organs either directly or indirectly. The oncogenic cascade always engages in the disruption of hormonal regulation and inflammatory responses, the induction of genomic instability and mutations, and the dysregulation of adult stem cell proliferation. This review aims to comprehensively summarize the existing evidence that points to the potential role of dysbiosis in the malignant transformation of extraintestinal organs such as the liver, breast, lung, and pancreas. Additionally, we delve into the limitations inherent in current methodologies, particularly the challenges associated with differentiating low loads gut-derived microbiome within tumors from potential sample contamination or symbiotic microorganisms. Although still controversial, an understanding of the contribution of translocated intestinal microbiota and their metabolites to the pathological continuum from chronic inflammation to tumors could offer a novel foundation for the development of targeted therapeutics.